Fertility intentions and perceived health status: A study of Polish migrants and non-migrants - Nasim Ahamed Mondal (Elsevier, 2024)
Aims: This study aims, probably for the first time, to compare the fertility intentions of migrants and non-migrants of the same nationality at origin based on their self-rated health, wellbeing, and gender. Methods: The study utilized data from the Families of Poles in the Netherlands (FPN) survey and the Generations and Gender Survey (GGS). This study used Blinder-Oaxaca decomposition models and generalized ordered logit models (gologit). Results: The findings reveal that both migrants and non-migrants who have good self-rated health and wellbeing are more likely to express a desire to have children in the short-term. The impact of perceived health on the intention to have children is significant for both female and male irrespective of their migration status. Additionally, the average fertility intentions score is higher for Polish migrants residing in the Netherlands compared to Polish non-migrants residing in Poland across the models. The study emphasizes the role good perceived health plays in shaping fertility intentions.